ENHANCEMENT OF NATURAL SCIENCE THROUGH INDIGENOUS MEDICINAL PLANTS - Muattar PANJIYEVA; Inoyat ELMURODOVA (Scholar Express Journal, 2024)
In the article, the use of more extensive information about local medicinal plants in the course of natural sciences in elementary grades is presented . Explaining to young students how useful and healing local plants growing in the territory of Uzbekistan and their effective use are of urgent importance today. The demand for medicinal plants growing in the territory of Uzbekistan is increasing day by day
Keywords: Local; medicinal flora; natural science; plants